Potential of Magnetic Hyperthermia to Stimulate Localized Immune Activation. Issue 14 (18th March 2021) - Carter, Thomas J.; Agliardi, Giulia; Lin, Fang‐Yu; Ellis, Matthew; Jones, Clare; Robson, Mathew; Richard‐Londt, Angela; Southern, Paul; Lythgoe, Mark; Zaw Thin, May; Ryzhov, Vyacheslav; de Rosales, Rafael T. M.; et al.
Abstract: Magnetic hyperthermia (MH) harnesses the heat‐releasing properties of superparamagnetic iron oxide nanoparticles (SPIONs) and has potential to stimulate immune activation in the tumor microenvironment whilst sparing surrounding normal tissues. To assess feasibility of localized MH in vivo, SPIONs are injected intratumorally and their fate tracked by Zirconium‐89‐positron emission tomography, histological analysis, and electron microscopy. Experiments show that an average of 49% (21–87%, n = 9) of SPIONs are retained within the tumor or immediately surrounding tissue. In situ heating is subsequently generated by exposure to an externally applied alternating magnetic field and monitored by thermal imaging. Tissue response to hyperthermia, measured by immunohistochemical image analysis, reveals specific and localized heat‐shock protein expression following treatment. Tumor growth inhibition is also observed. To evaluate the potential effects of MH on the immune landscape, flow cytometry is used to characterize immune cells from excised tumors and draining lymph nodes. Results show an influx of activated cytotoxic T cells, alongside an increase in proliferating regulatory T cells, following treatment. Complementary changes are found in draining lymph nodes. In conclusion, results indicate that biologically reactive MH is achievable in vivo and can generate localized changes consistent with an anti‐tumor immune response. Abstract : Localized heating is generated using superparamagnetic iron‐oxide nanoparticles (SPIONs) stimulated by an alternating magnetic field. A) Imaging of radiolabelled SPIONs enable real‐time fate tracking while B) SPION heating ability is monitored using thermal imaging. C) Heat‐shock responses within tumors and characterization of tumor infiltrating lymphocyte populations demonstrate localized immune activation.